2019
DOI: 10.1530/rep-18-0480
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of epididymosomes to the sperm small RNA profile

Abstract: It is now well established that mature spermatozoa harbour a rich and diverse profile of small non-protein-coding regulatory RNAs (sRNAs). There is also growing appreciation that this sRNA profile displays considerable plasticity, being altered in response to paternal exposure to a variety of environmental stressors. Coupled with evidence that upon delivery to the oocyte at the moment of fertilisation, sperm-borne sRNAs are able to influence both early embryonic development and the subsequent health of the off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(103 citation statements)
references
References 109 publications
0
93
1
Order By: Relevance
“…After leaving the testis, mammalian spermatozoa must transit the epididymis in order to acquire their forward motility properties and fertilizing ability . The epididymis is also responsible for sperm storage, and emerging evidence supports the concept that this male reproductive tract organ is the theater of sperm epigenome modifications involved in post‐fertilization events . Whereas the epididymis is part of the male reproductive tract of all vertebrate species practicing internal fertilization, the anatomy of this organ shows great phylogenetic variability even within the mammalian phylum .…”
Section: Introductionmentioning
confidence: 99%
“…After leaving the testis, mammalian spermatozoa must transit the epididymis in order to acquire their forward motility properties and fertilizing ability . The epididymis is also responsible for sperm storage, and emerging evidence supports the concept that this male reproductive tract organ is the theater of sperm epigenome modifications involved in post‐fertilization events . Whereas the epididymis is part of the male reproductive tract of all vertebrate species practicing internal fertilization, the anatomy of this organ shows great phylogenetic variability even within the mammalian phylum .…”
Section: Introductionmentioning
confidence: 99%
“…Region specific gene expression of epididymis in the mouse and human was also studied by microarray analysis(Johnston et al, 2005; Zhang et al, 2006). On the other hand, it was plausible that the epididymosome was contributed to the sperm modifications during the sperm transient in epididymis (Sharma et al, 2018; Trigg et al, 2019). Recently, James et al demonstrated the expression profiles of segment-specific human epididymal epithelial cells (Browne et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, epididymosomes are extracellular vesicles released by the epididymal epithelium, which encapsulate a macromolecular complex made up of proteins (required to avoid RNA degradation) and RNAs. During the sperm transit into the epididymis, epididymosomes interact with spermatozoa by modulating their RNA profile [11]. In more detail, while miRNAs are the most represented class of sRNA in the caput epididymis, tRFs are more abundantly found in the cauda [16,17].…”
Section: Seminal Plasma Transcriptomementioning
confidence: 99%
“…The seminal plasma (SP) is made-up of secretions arising from the male accessory glands, namely epididymis, seminal vesicles, and prostate. The SP is not only a medium for sperm transport, since it can modulate the female reproductive environment and immunity [9] to allow the acquisition of sperm competence [10] to influence sperm RNA content, and even embryo development, as transcriptome studies reveal [11]. In recent years, thousands of specific transcripts and proteins have been found in human seminal plasma (SP).…”
Section: Introductionmentioning
confidence: 99%